Penerapan Bot Telegram Berbasis Model Pembelajaran Discovery Learning di Kelas X Tata Busana 2 SMK Negeri 3 Kota Kediri - Hanifah Sa’diyah; Imami Arum Tri Rahayu; Peppy Mayasari; Mita Yuniati (Journal on Education, 2024)
This research was motivated by the lack of students participation in learning process, making students less active. The use of developments ICT in collaboration with learning models is used as an alternative solution to this problem. This research aims to increase students' activeness in participating in learning activities with the research subject being students of class X Fashion Design 2 at SMK Negeri 3 Kediri. The type of research used is Pre-Experimental with a One-Shot Case Study design. Data collection was carried out using observation sheet instruments, cognitive tests, and student response questionnaires. The research results showed of student activity observations reached 85% with a very good category. Student learning outcomes in the cognitive domain which obtained an average of 85.31 and the percentage of learning outcomes reaches 93,75% with very good criteria. Student responses obtained an average score of 3.37 with very good criteria. It can be interpreted, application of the Telegram Bot based on the Discovery Learning model is able to increase student activity, is feasible, interesting and easy to use in the learning material for textile fibers from cellulose in class X Fashion Design 2 at SMK Negeri 3 Kediri.